2021
DOI: 10.3390/antiox10081176
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cooking Methods on Bioactivity of Polyphenols in Purple Potatoes

Abstract: Purple-fleshed potato (Solanum tuberosum L.) is a good dietary source of anthocyanins, flavonols, and polyphenolic acids, mostly chlorogenic acid. The objective of this study was to examine the impacts of cooking methods including boiling, steaming, and the newly developed vacuum-sealed boiling (VSBoil) on extractability and bioactivity of polyphenolic compounds in a purple potato (PP) cultivar, Purple Pelisse. Data showed that boiling and steaming reduced the total polyphenolic content in PP. High-performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Our results were consistent with early studies ( Rytel et al, 2014 , Lemos et al, 2015 ), they reported that cooking had a detrimental effect on total phenolic, after roasting, boiling, microwaving and steaming, the total phenolic content decreased from 209 ± 35.7 mg GAE/100 g (fresh weight) to 38.1 ± 7.5, 137.6 ± 0, 74.0 ± 1.3, 130.4 ± 3.7 mg GAE/100 g (fresh weight), respectively. In another study, Sun et al (2021) also showed that boiling and steaming reduced the total polyphenolic content in potato. The decrease of total phenolic in cooked potato might attribute to the thermal-degradation or the leaching during cooking.…”
Section: Resultsmentioning
confidence: 90%
“…Our results were consistent with early studies ( Rytel et al, 2014 , Lemos et al, 2015 ), they reported that cooking had a detrimental effect on total phenolic, after roasting, boiling, microwaving and steaming, the total phenolic content decreased from 209 ± 35.7 mg GAE/100 g (fresh weight) to 38.1 ± 7.5, 137.6 ± 0, 74.0 ± 1.3, 130.4 ± 3.7 mg GAE/100 g (fresh weight), respectively. In another study, Sun et al (2021) also showed that boiling and steaming reduced the total polyphenolic content in potato. The decrease of total phenolic in cooked potato might attribute to the thermal-degradation or the leaching during cooking.…”
Section: Resultsmentioning
confidence: 90%
“…In addition, it is not only the natural food matrices that are essential [ 74 , 75 ], but also the preparation process and the conditions under which it is ingested (e.g., cooking, juicing, etc.). It has been widely demonstrated that cooking affects the phytochemical content of foods as well as their chemical structures and the bioavailability of their bioactive compounds; in other words, how a food is processed before consumption may be directly related to its health effects [ 76 , 77 , 78 , 79 , 80 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hamouz et al [49] reported a more than two to three times higher content of polyphenols in purple-fleshed potatoes compared to yellow-fleshed. Sun et al [10] reported a total polyphenol content in purple-fleshed potatoes at the level of 6.50 mg GAE g −1 DW. Our purple-fleshed potatoes (Violet Queen) harvested in September showed a higher TPC (33.4 mg GAE g −1 DW).…”
Section: Total Polyphenol Contentmentioning
confidence: 99%
“…In addition to essential macronutrients, potatoes also contain many phytonutrients such as polyphenols, anthocyanins, flavonoids, and carotenoids [1,10]. In plants, polyphe-nols play many endogenous roles, including plant growth and development, cell wall synthesis, and pigmentation, and have a protective effect, defending plants from biotic stress (insects, bacteria, viruses) and abiotic stress (UV radiation, free radicals) [2,11,12].…”
Section: Introductionmentioning
confidence: 99%